A symbiotic liaison between the genetic and epigenetic code - Heyn, Holger (Frontiers in Genetics, 2014)
With rapid advances in sequencing technologies, we are undergoing a paradigm shift from hypothesis- to data-driven research. Genome-wide profiling efforts gave informative insights into biological processes; however, considering the wealth of variation, the major challenge remains their meaningful interpretation. In particular sequence variation in non-coding contexts is often challenging to interpret. Here, data integration approaches for the identification of functional genetic variability represent a likely solution. Exemplary, functional linkage analysis integrating genotype and expression data determined regulatory quantitative trait loci (QTL) and proposed causal relationships. In addition to gene expression, epigenetic regulation and specifically DNA methylation was established as highly valuable surrogate mark for functional variance of the genetic code. Epigenetic modification served as powerful mediator trait to elucidate mechanisms forming phenotypes in health and disease. Particularly, integrative studies of genetic and DNA methylation data yet guided interpretation strategies of risk genotypes, but also proved their value for physiological traits, such as natural human variation and aging. This Perspective seeks to illustrate the power of data integration in the genomic era exemplified by DNA methylation quantitative trait loci (meQTLs). However, the model is further extendable to virtually all traceable molecular traits.